2013
DOI: 10.1684/agr.2013.0648
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of rice varietal diversity in the region of Vakinankaratra (Madagascar)

Abstract: Déterminants de la diversité variétale du riz dans la région de Vakinankaratra (Madagascar) Résumé Mieux connaître les dynamiques de l'agrobiodiversité est nécessaire pour intégrer sa préservation et sa valorisation dans les stratégies d'augmentation de la productivité agricole. La dynamique de la diversité variétale du riz a été analysée dans la région de Vakinankaratra, Madagascar, en 2006, à travers des enquêtes collectives et individuelles auprès d'un échantillon de 1 050 exploitations réparties dans 32 vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The average number of varieties cultivated per village in the study area is low compared to that found in the villages of the island of Madagascar (10.9; Radanielina et al 2013), Guinea (24.6;Barry et al 2008), and in the Kumaun region of Indian Central Himalaya (11; Agnihotri and Palni 2007). However, the diversity maintained at the household level (2.2) is almost similar to that held by Malagasy (Radanielina et al 2013), and Indian farmers (Laishram et al 2020), but lower than those held by Nepalese farmers (Bajracharya et al 2010). The low diversity observed at Igbo-Idé village could be explained by the fact that farmers of this village began to grown rice after recent sensitization campaigns carried out by government extension services and NGOs to promote the crop in the area considering that it is suitable for rice production: therefore, farmers grow only the recent rice varieties with high market value.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…The average number of varieties cultivated per village in the study area is low compared to that found in the villages of the island of Madagascar (10.9; Radanielina et al 2013), Guinea (24.6;Barry et al 2008), and in the Kumaun region of Indian Central Himalaya (11; Agnihotri and Palni 2007). However, the diversity maintained at the household level (2.2) is almost similar to that held by Malagasy (Radanielina et al 2013), and Indian farmers (Laishram et al 2020), but lower than those held by Nepalese farmers (Bajracharya et al 2010). The low diversity observed at Igbo-Idé village could be explained by the fact that farmers of this village began to grown rice after recent sensitization campaigns carried out by government extension services and NGOs to promote the crop in the area considering that it is suitable for rice production: therefore, farmers grow only the recent rice varieties with high market value.…”
Section: Discussionmentioning
confidence: 62%
“…Our results regrouped the rice accessions in 21 morphological groups based on seed characteristics. This diversity is very low compared to those found in Guinea (387 rice varieties; Barry et al 2008), in Bangladesh (670 unique rice varieties; Tiongco and Hossain 2015), and in Madagascar (346 rice varieties; Radanielina et al 2013). However, as in Lao (Appa Rao et al 2002), we noted that the same rice variety could be called by different names and different varieties could have the same name.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Geographic areas where farming systems, not yet affected by the Green Revolution, still rely on a large number of landraces constitute a good setting for such empirical analysis of the genetics of crop species adaptation to climate changes. Indeed, when spread over a broad environmental gradient, those landraces can collectively represent a meta-population harbouring large standing genetic variation (Barry et al 2007c ; Radanielina et al 2013 ), that has evolved historically through processes of human and natural selection (Bellon et al 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…Geographic areas where farming systems, not yet affected by the Green Revolution, still rely on a large number of landraces constitute a good setting for such empirical analysis of the genetics of crop species adaptation to climate changes. Indeed, when spread over a broad environmental gradient, those landraces can collectively represent a meta-population harbouring large standing genetic variation (Barry et al, 2007c; Radanielina et al, 2013).…”
Section: Introductionmentioning
confidence: 99%